Kelly and Her Baby / Watawat / The Tree is Awakened by the Memory of Her Leaves IV / Song Shu (Pine Tree) / The Tree is Awakened by the Memory of Her Leaves V / The Tree is Awakened by the Memory of Her Leaves / Soliloquy - Miclat, Maningning (Review of Women's Studies, 2008)
---